2011
DOI: 10.1186/1477-7517-8-25
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo-controlled, double-blind trial of Swedish snus for smoking reduction and cessation

Abstract: BackgroundEpidemiological studies suggest that smokeless tobacco in the form of Swedish snus has been used by many smokers in Scandinavia to quit smoking, but the efficacy of snus has so far not been evaluated in controlled clinical trials.MethodsWe conducted a randomized, double-blind, placebo-controlled, clinical trial aimed at assessing the efficacy of snus to help adult cigarette smokers in Serbia to substantially reduce, and, eventually, completely stop smoking. The study enrolled 319 healthy smokers aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 21 publications
5
43
0
Order By: Relevance
“…Specifically, individuals instructed to use snus as a means of coping with smoking restrictions reported a reduction in cigarettes per day that was far lower than that reported by those instructed to use snus as a means of smoking reduction (Burris et al, 2014). Furthermore, among smokers who report readiness to quit, snus use shows some efficacy for smoking cessation in randomized clinical trials (Fagerstrom, Rutqvist, & Hughes, 2012; Hatsukami et al, 2015; Joksić, Spasojević-Tišma, Antić, Nilsson, & Rutqvist, 2011; Tønnesen, Mikkelsen, & Bremann, 2008). Consequently, if the tobacco control community chooses to advocate for snus as a means of harm reduction–a topic which is still up for debate (Hatsukami, Ebbert, Feuer, Stepanov, & Hecht, 2007; Hatsukami, Lemmonds, & Tomar, 2004; Levy et al, 2006; O’Connor, 2012; Tomar, 2007)–then messaging around the purpose of snus use must be clear.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, individuals instructed to use snus as a means of coping with smoking restrictions reported a reduction in cigarettes per day that was far lower than that reported by those instructed to use snus as a means of smoking reduction (Burris et al, 2014). Furthermore, among smokers who report readiness to quit, snus use shows some efficacy for smoking cessation in randomized clinical trials (Fagerstrom, Rutqvist, & Hughes, 2012; Hatsukami et al, 2015; Joksić, Spasojević-Tišma, Antić, Nilsson, & Rutqvist, 2011; Tønnesen, Mikkelsen, & Bremann, 2008). Consequently, if the tobacco control community chooses to advocate for snus as a means of harm reduction–a topic which is still up for debate (Hatsukami, Ebbert, Feuer, Stepanov, & Hecht, 2007; Hatsukami, Lemmonds, & Tomar, 2004; Levy et al, 2006; O’Connor, 2012; Tomar, 2007)–then messaging around the purpose of snus use must be clear.…”
Section: Discussionmentioning
confidence: 99%
“…24 Abstinence from cigarettes was nearly identical after 3 months of follow-up (27% vs 25%; independently calculated relative risk=1.1). A separate meta-analysis of only the Fagerström (US) 23 and Joksić (Serbian) 22 RCTs suggested a threefold increase in abstinence in favour of snus. 25 The existing evidence leads to the following inferences: (1) only a small number of randomised trials have tested the impact of snus on smoking behaviour, (2) most studies suggest positive (or sometimes non-significant) effects from snus; no published study has shown negative effects on quitting and (3) all randomised trials, to date, have been abstinence focused, recruiting smokers wanting to quit and providing snus with explicit instructions to do so.…”
Section: Introductionmentioning
confidence: 98%
“…Abstinence rates were significantly higher at 7 weeks of follow-up (36% vs. 21%; Odds Ratio/OR = 2.1) but did not persist after six months (23% vs. 21%; OR = 1.3). A larger, longer and placebo-controlled study from Serbia found a 3-fold increase in abstinence at 6 months (9.5% vs. 3.7%, Adjusted Odds Ratio/AOR = 2.7), and a nearly 2-fold increase at one year (15.8% vs. 9.3%, AOR = 1.9 [22]. Among smokers wanting to stop smoking, this evidence suggests snus might be an effective substitute for cigarettes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations